Population origin determines the adaptive potential for the advancement of flowering onset in Lupinus angustifolius L. (Fabaceae) - Sandra Sacristán‐Bajo; Alfredo García‐Fernández; Carlos Lara‐Romero; Samuel Prieto‐Benítez; Pablo Tabarés; Javier Morente‐López; María Luisa Rubio Teso; Aitor Alameda‐Martín; Elena Torres; José María Iriondo (Evolutionary Applications, 2023)
Abstract In the present framework of global warming, it is unclear whether evolutionary adaptation can happen quick enough to preserve the persistence of many species. Specifically, we lack knowledge about the adaptive potential of the different populations in relation to the various constraints that may hamper particular adaptations. There is evidence indicating that early flowering often provides an adaptive advantage to plants in temperate zones in response to global warming. Thus, the objective of this study was to assess the adaptive potential for advancing flowering onset in Lupinus angustifolius L. (Fabaceae). Seeds from four populations from two contrasting latitudes in Spain were collected and sown in a common garden environment. Selecting the 25% of the individuals that flowered earlier in the first generation, over three generations, three different early flowering selection lines were established, involving both self‐crosses and outcrosses. All artificial selection lines advanced their flowering significantly with respect to the control line in the northernmost populations, but not in the southern ones. Selection lines obtained from outcrossing had a greater advancement in flowering than those from self‐crossing. No differences were found in the number or weight of the seeds produced between control and artificial selection lines, probably because plants in the common garden were drip irrigated. These results suggest that northern populations may have a greater adaptive potential and that southern populations may be more vulnerable in the context of climate warming. However, earlier flowering was also associated with changes in other traits (height, biomass, shoot growth, specific leaflet area, and leaflet dry matter content), and the effects of these changes varied greatly depending on the latitude of the population and selection line. Assessments of the ability of populations to cope with climate change through this and other approaches are essential to manage species and populations in a more efficient way.